Pengaruh Kualitas Pelayanan Terhadap Loyalitas Pelanggan Melalui Kepercayaan Sebagai Mediasi pada Puri Laundry: Penelitian - Anak Agung Ngurah Bagus Narendra; I Gusti Ayu Tirtayani; Nyoman Sri Manik Parasari; Ni Putu Nina Eka Lestari (Journal of Innovative and Creativity, 2025)
This study aims to determine the effect of service quality on customer loyalty with trust as a mediating variable at Puri Laundry located at Jalan Tukad Punggawa No. 18, Dauh Puri Klod, South Denpasar, Denpasar City, Bali. The background of this study departs from the phenomenon of declining profits and customers switching to other service providers after employee turnover, which is indicated to be influenced by a decline in service quality and a decline in customer trust. This study uses a quantitative approach with a causal research design. Data were obtained by distributing questionnaires to 95 customers selected using a stratified random sampling technique from a total population of 2,137 customers. Variable measurement uses a five-point Likert scale, and data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results show that service quality has a positive and significant effect on trust, so that the better the quality of service provided, the higher the level of customer trust. Trust is also proven to have a positive and significant effect on customer loyalty, which indicates that customer confidence in the security, consistency, and reliability of services can encourage loyal behavior. However, service quality did not have a significant direct effect on customer loyalty, indicating that service improvements do not necessarily lead to loyalty without trust. This study also found that trust significantly mediated the relationship between service quality and customer loyalty, making trust a key element bridging customer perceptions of service and their decision to remain loyal.